Analisis Studi Literatur Pemanfaatan Medan Elektromagnetik pada Perangkat Navigasi dalam Kehidupan Sehari-hari - Lelis Reminis There Gulo; Desta Adji Saputra; Muhammad Azka Alwafi; Gunawan Gunawan; Diyajeng Luluk Karlina (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This research discusses the utilization of electromagnetic fields in navigation devices, which play a crucial role in daily life. With technological advancements, navigation systems such as GPS, radar, and compasses have become essential tools for determining position and direction. This study employs a literature review method, which involves a series of activities related to collecting library data, reading, recording, and processing relevant information for the research objective. The aim is to analyze various sources of information regarding the use of electromagnetic fields in these devices. The findings indicate that electromagnetic fields enable navigation devices to function effectively, despite challenges such as signal interference and weather conditions that may reduce accuracy. This research aims to explore how electromagnetic fields, which combine electric and magnetic fields, are utilized in modern navigation systems. The method used is a literature review, where the researchers collect and analyze information from various reliable sources to understand the effectiveness and challenges in the application of electromagnetic fields in these devices. The results show that electromagnetic fields allow navigation devices to operate effectively, providing accurate location information